1989
DOI: 10.1104/pp.90.2.679
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of 2-Carboxy-d-Arabinitol 1-Phosphatase

Abstract: Carboxyarabinitol 1-phosphatase (2-carboxy-D-arabinitol 1-phosphate phosphohydrolase), a chloroplast enzyme that metabolizes the naturally occurring inhibitor of ribulose-1,5-bisphosphate carboxylase/oxygenase, was isolated from tobacco (Nicotiana tabacum) leaves. The enzyme was purified more than 3500-fold using a protocol that included ammonium sulfate fractionafton and gel filtration, ion-exchange, and hydrophobic interaction chromatography. Analysis of the final preparation by sodium dodecyl sulfate polyac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
(54 reference statements)
0
22
1
Order By: Relevance
“…They isolated leaf chloroplastic, cytoplasmic, and vacuolar materials by the non-aqueous fractionation method to conclude that CAIP and CA1P phosphatase did occur in chloroplasts [27]. It has also been reported that CA1P phosphatase can occur in both cytoplasm and chloroplasts of tobacco leaves [15]. However, the whole leaves were ground in liquid N2 or an isotonic medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They isolated leaf chloroplastic, cytoplasmic, and vacuolar materials by the non-aqueous fractionation method to conclude that CAIP and CA1P phosphatase did occur in chloroplasts [27]. It has also been reported that CA1P phosphatase can occur in both cytoplasm and chloroplasts of tobacco leaves [15]. However, the whole leaves were ground in liquid N2 or an isotonic medium.…”
Section: Discussionmentioning
confidence: 99%
“…2-Carboxyarabinitol 1-phosphate (CA1P) may be synthesized in the night to inhibit the activated form of the enzyme in plants including beans, tobacco, and cucumber [2][3][4][5][6][7][8][9][10][11][12][13]. CAIP that accumulates and is bound to RuBisCO in the night is released from the enzyme by RuBisCO activase and degraded [12,14,15]. However, the amount of CA1P in the leaves of these plants varies widely, up to a level more than the concentration of the active sites of RuBisCO in the stroma in Phaseolus, although the amount increases least in tobacco [3,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…This implies an interaction between CA 1-P metabolism and reactions on the reducing side of PSI. Additionally, in preliminary studies, it has been noted that CA 1-Pase activity is stimulated in vitro by several chloroplast metabolites, including NADPH, RuBP, and FBP (7,20). With P. vulgaris, appreciable levels of CA 1-P accumulation occur within 60 s under low-light conditions, but in other species the increase in inhibitor concentration may require more than 1 h (6, 10).…”
mentioning
confidence: 99%
“…We also present information concerning the thermal stability of CA l-Pase activity, allowing a comparison to the established heat sensitivity of Rubisco activase ( 17 (20). Reactions were initiated by adding the enzyme and terminated after 10 min by the addition of 0.1 mL of0.5 N HCOOH.…”
mentioning
confidence: 99%
“…Feeding DCMU (18), nigericin, or methyl viologen (15) to leaf discs prevents the lightdependent removal of CAl P from rubisco, indicating the involvement of photosynthetic electron transport. Recently, a protein effective in hydrolyzing CAI P to CA was purified from tobacco chloroplasts (6,16). The protein had a high affinity for hydrolyzing CAl P but was ineffective against other phosphate esters.…”
Section: Degradation and Synthesis Of Calpmentioning
confidence: 99%